Gas chromatography-mass spectrometry based metabolomics to Identify the alpha glucosidase inhibitors from flesh of salacca zalacca fruits and their molecular docking studies - Saleh, Mohammed S M; Mat So'ad, Siti Zaiton; Ahmed, Qamar Uddin; Ibrahim, Zalikha; Siddiqui, Mohammad Jamshed Ahmad (Medknow, 2020)
Introduction: Salak fruit (Salacca zalacca) is traditionally used and commercialized as an antidiabetic agent. However, the scientific evidence to proof this usage is quiet lacking. Objectives: This research was aimed to evaluate the antidiabetic activity of S. zalacca fruit using α-glucosidase enzyme and profiling the identified antidiabetic agents using gas chromatography-mass spectrometry (GCMS). Material and Methods: For metabolomics study, the fruit was extracted by different ratios of ethanol and water (0, 20, 40, 60, 80, 100%, v/v) to get E0 (100% water), E20 (20% ethanol), E40 (40% ethanol), E60 (60% ethanol), E80 (80% ethanol) and E100 (100% ethanol). The α-glucosidase enzyme was used in determining the α-glucosidase inhibitory activity. Results: The 60% aqueous ethanolic extract exhibited the highest bioactivity (IC50 16.90 μg/mL). Several α-glucosidase inhibitors such as stearic acid, palmitic acid, β-Sitosterol, myo-inositol were identified by GC-MS. The docking results predicted the interactions of all the metabolites identified to be in non-competitive mode involving majorly hydrophobic interactions with the protein residues. Some of the residues involved are PRO456, AGR467, LYS406 HID295, ASN259 LEU313, LYS125 H-bond HIE315, ARG315, PHE303. Conclusion: The in vitro assay strongly suggests that E60 extract from S. zalacca fruit is having potential antidiabetic activity. Addition of extra hydrophobic groups on palmitic acid and ß-sitosterol would increase the inhibitory activity.